PENGARUH PIJAT OKETANI DAN EDUKASI MENYUSUI BERBASIS VIDEO TERHADAP BREASFEEDING SELF EFFICACY PADA IBU NIFAS - Tentya Indah Masfufa; Wan Anita; Yadriati Maya Pesa (Ensiklopedia of Journal, 2026)
Breast milk is the best nutrient for the growth and development of infants. The achievement of exclusive breastfeeding in Indonesia (74.5%) is still far from the national target of 80%. One of the contributing factors is less milk production. Oketani massage makes the breasts softer, the areolas and nipples more elastic, making it easier for the baby to suckle. Education can increase knowledge and abilities and skills of mothers. Oketani massage and breastfeeding education can help increase milk production.Objective : Proving the effect of oketani massage intervention and breastfeeding education on breastfeeding self-efficacy in postpartum mothers Method : Quasy experiment with Design Pretest and Posttest With Group control. The sample consisted of 34 postpartum mothers, each group consisting of 17 respondents. The intervention group was given oketani massage and breastfeeding education while the control group was given health education about breastfeeding for 7 days. The data collected is breast-feeding self-efficacy filling out questionnaires. Data analysis used the Wilcoxon test, Mann-Whitney, Independent T-Test.Results : The mean difference in pre-post breastfeeding self-efficacy in the intervention group was 5.59 and -0.82 in the control group (p value 0.000).Conclusion : Giving oketani massage and breastfeeding education can increase breastfeeding self-efficacy in postpartum mothers.Keywords : Breastfeeding Self Efficacy, Breastfeeding Education, Oketani Massage, Postpartum Mother